TINGKAT PENDIDIKAN TERHADAP PARTISIPASI MASYARAKAT PADA LEMBAGA PEMBERDAYAAN MASYARAKAT DI KELURAHAN BATU - Ismail B; Muhammad Rais Rahmat R; Haeruddin Syarifuddin (PRAJA: Jurnal Ilmiah Pemerintahan, 2021)
This study aims to determine the effect of education level on community participation in community empowerment institutions in Batu Village, Pitu Riase District, Sidenreng Rappang Regency. The method used in this study is a descriptive research method with a quantitative approach. In general, this study uses inductive statistics to analyze research data. Based on the results of these studies indicate that the level of education is needed in the community in order to improve the development of human resources, especially in planning, implementing and supervising development in Batu Village. People who are highly educated are quicker to understand and understand the development programs that will be implemented. They are also expected to motivate other communities to participate in development activities in the Kelurahan in order to realize the common goals of the community for the progress of the region.